An observation into large group teaching - Cejnar, Leela (Penerbit Universiti Kebangsaan Malaysia, 2015)
This article is based on our personal reflections of our teaching practices as the convenor of a large introductory business law course. The challenges is that teaching this course presents can be attributed as much to its size as to the fact that the students are not law students but rather, are from a business discipline. For most of them, this is one of their first university courses and almost certainly, the first law course to which they are exposed. In terms of size, this course can be considered as a “large course” with typically around 500 to 700 students in each cohort, annually. This article investigates some of the challenges faced by a large group of teachers, including by comparing our own approach to teach and our teaching rationale with those adopted by other “large group” teachers, through a review of educational literature.